Stream Sediment Geochemical Survey around Mildo and Its Environs, Madagali, Northeastern Nigeria - Ahmed, H. A.; Halilu, M.; Saleh, M.B.; Hassan, A. (IJRDO-Journal of Applied Science, 2017)
In an attempt to explore the mineral potentials of Mildo area, geology and stream sedimentsgeochemical survey around Mildo and its environs, Madagali area, Northeastern Nigeria wascarried out. The area is part of Mandara Mountains. The Mandara Mountains together with theadjacent Hawal and Adamawa Massif form the northeastern basement complex. Streamsediments were collected at the confluence points of two or more streams mostly at a depth of 20– 30cm. The stream sediment samples were analyzed for trace and major elemental concentrationusing XRF analytical method. The result of the geochemical analysis was thereafter subjected tostatistical analysis. Elements of high concentrations were identified and they include Ba, Ti, Fe,Zn, Cu, Hg, Cd, Co, Zr, Sr and Ag. Locations SSP4 and SSP13 have concentrations of theseelements in high values. We speculate that high concentration of Ag can be associated withmineralization of gold and other Platinum Group Metals in the area. Although, most elementsstudied have high concentrations, but they fall short of threshold values to be considered asanomalous to constitute an economic deposit. However, we recommend further surveys in thevicinity of areas with highest concentrations for possible location of economic depositsupstream